Antitumor and antiangiogenic activity of the novel chimeric inhibitor animacroxam in testicular germ cell cancer. Issue 12 (22nd October 2019) - Steinemann, Gustav; Dittmer, Alexandra; Schmidt, Jacob; Josuttis, David; Fähling, Michael; Biersack, Bernhard; Beindorff, Nicola; Jolante Koziolek, Eva; Schobert, Rainer; Brenner, Winfried; Müller, Thomas; Nitzsche, Bianca; et al.
Abstract : Chimeric inhibitors, which merge two drug pharmacophores in a single molecule have become a prominent approach for the design of novel anticancer compounds. Here, we examined animacroxam, which combines histone deacetylase (HDAC) inhibitory and cytoskeleton‐interfering pharmacophores, in testicular germ cell tumors (TGCT). The effectiveness of animacroxam was compared to that of the commonly applied chemotherapeutic cisplatin as well as the clinically approved HDAC inhibitor vorinostat. The antineoplastic and antiangiogenic effects of animacroxam on TGCT in vivo were assessed through exploratory animal studies and a modified chorioallantoic membrane assay, revealing that animacroxam has significant antitumor activity in TGCT. A novel positron emission tomography/MR‐imaging approach was applied to determine tumor volume and glucose [2‐fluoro‐2‐deoxy‐d‐glucose (18F‐FDG)] uptake in TGCT tumors, revealing reduced glucose uptake in animacroxam‐treated TGCTs and showing a dose‐dependent suppression of glycolytic enzymes, which led to a breakdown in glycolytic energy production. Furthermore, the observed antiangiogenic effects of animacroxam were related to its ability to inhibit endothelial cell–cell communication, as the expression of gap junction‐forming connexin 43 was strongly suppressed, and gap‐junctional intercellular mass transport was reduced. Our data suggest that the chimeric HDAC inhibitor animacroxam may become a promising candidate for the treatment of solid cancers and may serve as an interesting alternative to platinum‐based therapies. Abstract : The chimeric inhibitor animacroxam combining histone deacetylase (HDAC)‐inhibiting and cytoskeleton‐interfering pharmacophores exerts pronounced antineoplastic efficiency. Animacroxam‐inhibited tumor growth is associated with a breakdown of tumor cell glucose metabolism and antiangiogenic effects involving the disruption of endothelial cell–cell communication. As the effectiveness of the novel chimeric inhibitor goes beyond that of HDAC inhibition alone, animacroxam may become an interesting compound for future cancer therapy.